Clusters Structure, Bonding and Reactivity - Nguyen, Minh Tho; Kiran, Boggavarapu (Challenges and Advances in Computational Chemistry and Physics, 2017)
The field of atomic clusters continues to attract great interest amongst physicists and chemists alike. This is in part due to their intrinsic properties and potential industrial applications. The first part of Binary Clusters is devoted to recent developments in experimental techniques, the second part covers a variety of theoretical approaches. Different theoretical methods based on group/graph theories and quantum chemical computational methods as well as various spectroscopy techniques (such as mass, laser, infrared, photoelectron etc.) are applied to the determination of the existence of geometrical and electronic structures, chemical bonding phenomena, and the thermodynamic stabilities of several classes of binary clusters. All chapters within this review volume have been contributed by experts in chemistry, physics, and material sciences based at the University of Leuven, Belgium. This book is aimed at professionals and students working in cluster science.